Expression and clinical significance of inhibitory receptor Leukocyte-associated immunoglobulin-like receptor-1 on peripheral blood T cells of chronic hepatitis B patients: A cross-sectional study. Issue 29 (23rd July 2021) - Gu, Yurong; Bi, Yanhua; Wei, Huan; Li, Jing; Huang, Zexuan; Liao, Chunhong; Liao, Weixin; Huang, Yuehua
Abstract : Abstract: Leukocyte-associated immunoglobulin-like receptor-1 (LAIR-1) is an inhibitory receptor that is expressed on the surface of multiple immune cells and plays key roles in immune modulation. In patients with chronic hepatitis B (CHB), T cell number and functions are abnormal and the expression of inhibitory receptors is elevated. However, the expression of LAIR-1 on T cells in patients with CHB is still undetermined. We recruited 320 patients with CHB in different disease phases and 17 healthy donors. Serum biochemical and virological examinations were performed for each participant, and their demographic and clinical data were collected. According to the latest American Association for the Study of Liver Disease guidelines, we categorized the patients into 4 groups: immune active, immune tolerant, inactive CHB, and gray zone. Additionally, we tested the expression of LAIR-1 on T cells and T cell subsets using flow cytometry. We observed a significant decrease in LAIR-1 expression on CD3+ T cells and its two subsets (CD4+ and CD8+ T cells) in patients with CHB. LAIR-1 expression on T cells was the lowest in the immune active group. LAIR-1 expression levels on CD4+ and CD8+ T cells showed a significant negative association with hepatitis B virus (HBV) DNA load and were lower in hepatitis B e antigen (HBeAg)-positive patients than in HBeAg-negative patients ( P  < .05). In addition, LAIR-1 expression levels on CD3+, CD4+, and CD8+ T cells were all negatively associated with liver inflammation and fibrosis parameters, such as alanine aminotransferase and aspartate aminotransferase levels, FibroScan value, and aspartate aminotransferase-to-platelet ratio index score. LAIR-1 expression levels on T cells were associated with HBV DNA load and liver inflammation and fibrosis parameters, indicating that LAIR-1 may play an important regulatory role in HBV-induced T cell immune pathogenesis and may be a therapeutic target for CHB. Abstract : Supplemental Digital Content is available in the text